Donor liver apoptosis is associated with early allograft dysfunction and decreased short‐term graft survival after liver transplantation. Issue 12 (22nd November 2018) - Zhu, Zebin; Tang, Yunhua; Huang, Shanzhou; Zhao, Qiang; Schroder, Paul M.; Zhang, Zhiheng; Zhang, Yixi; Sun, Chengjun; Wang, Linhe; Ju, Weiqiang; Wang, Dongping; Guo, Zhiyong; et al.
Abstract: Background: The clinical significance of apoptosis in assessing the quality of donor liver grafts remains unknown. Aims: This study aimed to determine whether apoptosis in a donor liver is predictive of early allograft dysfunction (EAD) and graft survival after liver transplantation (LT). Methods: Donor liver specimens were analyzed for apoptosis using TUNEL assays. The prognostic factors for EAD were identified through logistic regression analyses, and a nomogram was developed. Results: The apoptosis index of donor livers in EAD patients was significantly higher than that of donors livers in non‐EAD patients (median 5.3; interquartile range [IQR] 3.4 vs 3.5; 3.6, P  < 0.001). Multivariate analyses identified the apoptosis index of the donor liver (HR = 6.927, P  < 0.001) and five other characteristics as independent predictors of EAD. A nomogram built on these predictive variables showed good calibration and discriminatory abilities, with a c‐index value of 0.847. The 30‐day graft survival rates in the high apoptosis index (apoptosis index >4.4%) group were significantly lower than those in the low apoptosis index (apoptosis index ≤4.4%) group (84.4% vs 97.6%, P  = 0.004). Conclusions: Donor liver apoptosis plays a significant role in predicting EAD after LT. Furthermore, a high apoptosis index in the donor liver was associated with inferior graft survival in the short‐term.